Time Series and Cross-Sectional Analysis of Tobacco Companies for the 2021–2024 Period Case Study: PT Indonesian Tobacco Tbk, PT Gudang Garam Tbk, and PT HM Sampoerna Tbk - Rafif Putra W; Lufvi Selvia Febrianti; Muhammad Iqbal Ainur R; Cholis Hidayati (Journal of Business Economics and Agribusiness, 2026)
This study aims to analyze and compare the financial performance of PT HM Sampoerna Tbk, PT Gudang Garam Tbk, and PT Indonesian Tobacco Tbk during the 2021–2024 period using time series and cross-sectional approaches. The research employs a quantitative descriptive method based on secondary data obtained from audited annual financial statements published by the Indonesia Stock Exchange. Financial performance is measured using liquidity, activity, solvency, and profitability ratios. Time series analysis is applied to observe performance trends over four years, while cross-sectional analysis is used to compare company performance in the 2024 fiscal year. The results show that PT HM Sampoerna Tbk demonstrates the most balanced and stable financial performance, characterized by efficient asset utilization, strong solvency, and consistent profitability. PT Gudang Garam Tbk exhibits very strong liquidity and a conservative capital structure, but relatively lower operational efficiency and profitability. Meanwhile, PT Indonesian Tobacco Tbk shows higher profit potential accompanied by declining liquidity, increasing leverage, and greater financial risk. In conclusion, differences in company scale, operational efficiency, and financial strategy significantly influence financial sustainability in the Indonesian tobacco industry.